Developing a Cutting Tool with Mild Steel for Printed Circuit Board - M. M., Noor; M. M., Rahman; K., Kadirgama; M. R. M., Rejab; Z., Ghazalli; M. A., Hassan (2008)
This paper describes the design and fabrication of a cutter using mild steel for the printed circuit board. The board contains cuprum as a trace to connect the electricity current to electronic component like resistors and capacitors. The printed circuit board was widely used in electronic and electric components. The normal way to cut the printed circuit board is using hand due to the sensitive of it. By developing the cutter, it is easy to cut the printed circuit board with more efficient without damaging the board. The performance of the cutter that fabricates using mild steel is only average due to its hardness. It becomes dull very fast.